Evaluating the Impact of Value-Added Tax on Income Inequality in EU Member States - Kratina, Ondřej; Šváb, Patrik; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The bachelor's thesis evaluates the impact of value-added tax (VAT) on income inequality in the member states of the European Union. The first chapter focuses on the concept of income inequality and its relationship to tax policy, with an emphasis on theoretical foundations and the role of fiscal policy in reducing inequality within the EU. The second chapter concentrates on the VAT system, examining its structure, function, and significance in the European context, including its potential redistributive effects. The third chapter presents an empirical analysis based on panel data from EU member states, assessing the influence of VAT on income inequality. The control variables include unemployment, education, and trade openness. GDP per capita is subsequently included as a robustness check. The results show that although VAT plays an important role in national tax systems, its redistributive effect on income inequality weakens after accounting for GDP per capita. The thesis provides insights into the role of indirect taxation in shaping income distribution within the EU.
Vedoucí práce: Patrik Šváb
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses